MENGEMBANGKAN PEMBELAJARAN SASTRA DI SEKOLAH DASAR - Mutmaina, Yusnianti Nurul; Hamzah, Rahma Ashari (Universitas Tanjungpura, 2025)
Literature learning at the elementary school level plays a strategic role in developing students’ language skills, literacy competence, and character formation. However, current practices indicate that literature learning in elementary schools has not been optimally implemented. Instructional activities are still dominated by mechanical approaches such as reading texts and answering questions, which limit students’ opportunities to experience meaningful literary appreciation. This study aims to examine the current condition of literature learning in elementary schools, identify effective contextual instructional strategies, and analyze the challenges faced by teachers in implementing innovative literature learning. This study employs a literature review method by analyzing relevant national accredited journals and reputable international publications. The review process includes literature collection, selection based on relevance and recency, content analysis, and synthesis of research findings. The results show that literature learning in elementary schools faces several challenges, including limited instructional strategies, low teacher creativity, insufficient learning resources, and minimal use of innovative media. Nevertheless, various studies indicate that innovative approache—such as Literature-Based Instruction, integration of literature with ecoliteracy, utilization of digital and game-based learning media, and local wisdom–based models—are effective in enhancing students’ engagement, literacy skills, and character development. Therefore, a strategic shift toward aesthetic and experiential literature learning is necessary. Strengthening teacher professional competence, enriching learning resources, and optimizing educational technology are essential to creating meaningful literature learning experiences that support literacy and character education in elementary schools.